Clinico-hematological profile of chronic lymphoproliferative disorders in patients presenting with lymphocytosis - Rashid, Anila; Syed Saqlain Ali Meerza,; Huma Mansoori,; Muhammad Shariq Shaikh, (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the spectrum and clinico-haematological profile of chronic lymphoproliferative disorders in patients presenting with lymphocytosis. Method: The cross-sectional, retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data related to cases of bone marrow aspirate and trephine from January to November 2020. Patients for whom the bone marrow was done for lymphocytosis were studied for the presence of lymphoproliferative disorders, sub-types and patients’ characteristics. The diagnosis and classification were based on the World Health Organisation criteria for tumours of haematopoietic and lymphoid tissues. Data was analysed using SPSS 21. Results: Of the 3,334 bone marrow specimens tested, 103(3%) were related to lymphocytosis. Of these, 84(82%) were diagnosed with lymphoproliferative disorders, while diagnosis remained undetermined in 19(18%) cases. Male:female ratio was 3.6:1 and median age was 60 years (range: 21-85 years). Constitutional symptoms were found in 61(73%) patients. Median absolute lymphocyte count was 45x109/L (range: 5.3-480). All 84(100%) patients were classified as B-cell lymphoproliferative disorder. Chronic lymphocytic leukaemia was the most common form, 61(73%), and 31(51%) of them presented with advanced stage disease. Conclusion: A huge majority of patients presenting with lymphocytosis had underlying lymphoproliferative disorders of which B-cell chronic lymphocytic leukaemia was found to be the most common. Key Words: Lymphoproliferative disorder, Lymphocytosis, Chronic lymphocytic leukaemia, Bone marrow, Pakistan.